Estudo comparativo de métodos digitais de captura de realidade para levantamento cadastral de edificações históricas - Ciro Junior Martins Ribeiro (2023)
The forms of representation of architectural projects and buildings are in constant evolution, guided by the needs of the times and available techniques. The documental record of the built heritage, in addition to guaranteeing the preservation of memory and history, is an important instrument for those who intend to intervene in the heritage asset. In addition, it enables a more accurate understanding of the evolutions that occurred in the “architectural organism”, in the structures and in all the complexity of the building, surpassing the material and tangible sphere. The documentation of cultural assets often presents itself in a deficient heterogeneity of formats and accesses, or even in the absence of information about the asset. There is a demand for improvement in built heritage document methodologies, and another for efficiency and effectiveness in survey methods and projects with complex models. Corresponding to the exposed issues, Digital Heritage and digital reality capture techniques emerge to present possible solutions to many of these issues, making document processes faster, more accessible and more complete. The digital reality capture methods enhance the quality of the construction process and the quality of the final products from cadastral surveys of built heritage. Despite this, there is still strict disclosure (practical and theoretical) about detailed aspects of these methods. Even if one is aware of its existence and efficiency, and even if one wants to take advantage of it for a procedural and qualitative gain, the very choice of the method can be confused in the methodological options due to lack of knowledge of the details and characteristics of each one. This experimental research aims to compare reality capture methods. At first, the comparison is made between photogrammetry – more specifically the DSM -, and terrestrial laser scanning. In a second moment, compare the photogrammetry with a portable device with Lidar sensor. In the comparative experiments carried out, a large number of variables can be analyzed simultaneously in order to define the final quality of each one. The methods have very specific advantages and disadvantages that directly influence the characteristics of the final product, and the level of control that can be had in the process of using them for capture.